Association of Echocardiographic Epicardial Fat Thickness and Carotid Intima Media Thickness with the Severity of Coronary Artery Disease - Hussein, Muataz F; Hussein, Hafidh J (AL-Kindy College Medical Journal, 2020)
Background: Coronary artery disease remains the main cause of death despite several preventive programs. Epicardial adipose tissue is a visceral fat depot of the heart located along the large coronary arteries and on the surface of ventricles and apex. Intima media thickness is commonly recognized as the initial stage in the development of atherosclerosis. The development of ultrasound machines, advances in echocardiographic devices and high resolution transducers facilitate comprehensive analysis of epicardial fat thickness (EFT) and carotid –intima media thickness (C-IMT).Aim: To investigate the relationship of echocardiographic epicardial fat thickness (EFT) and carotid –intima media thickness (C-IMT) with the severity of coronary artery disease.Methods: A cross sectional multicenter diagnostic accuracy study carried out at Ibn Al-Nafis Cardiovascular Hospital, Ibn Al- Bitar Cardiology Center and Ghazi Al-Hariri Hospital –Iraqi Center for Cardiology during the period between October 2016 and May 2017 assessing. History regarding demographic data and risk factors was taken. Two dimensional transthoracic echocardiographic measurements were done. EFT was measured from parasternal long axis view perpendicular to the right ventricular free wall. C-IMT was measured according to that recommended by the American society of echocardiography (ASE).Results: The current study demonstrated that the EFT has a direct and significant correlation with the number of involved vessels (P value ˂ 0.001, r= 0.770). The validity of EFT to discriminate between multiple vessels disease and no vessel involvement is excellent (AUC= 0.984, cut point > 8mm, sensitivity=92.9%, specificity= 93.3%). There is inverse and significant correlation between ejection fraction (EF) and three vessels disease (P value ˂ 0.001, r= -0.507). Also there is a direct and significant correlation between C-IMT and severity of CAD. ROC analysis for validity of C-IMT to discriminate between multiple vessels disease and no vessel involvement is excellent (AUC= 0.961, cut point > 1.04mm, sensitivity=92.9%. specificity=86.7%). C-IMT is fair to discriminate between single vessel disease and no vessel involvement (AUC=0.738, cut point ˃ 0.84mm, sensitivity 100%), so if correlated with age, C-IMT above 0.84 can be used as a cut off point for the prediction of CAD. Finally, EFT and C-IMT are more likely to reflect severity of CAD than their ratio.Conclusions: C-IMT and EFT are simple and reproducible parameters that can be used as a screening tool for the presence and severity of CAD especially before symptoms appearance in high risk patients